Efficacy and safety of early treatment with sarilumab in hospitalised adults with COVID-19 presenting cytokine release syndrome (SARICOR STUDY): protocol of a phase II, open-label, randomised, multicentre, controlled clinical trial. Issue 11 (14th November 2020) - León López, Rafael; Fernández, Sheila Cárcel; Limia Pérez, Laura; Romero Palacios, Alberto; Fernández-Roldán, María Concepción; Aguilar Alonso, Eduardo; Pérez Camacho, Inés; Rodriguez-Baño, Jesús; Merchante, Nicolás; Olalla, Julián; Esteban-Moreno, M Ángeles; Santos, Marta; et al.
Abstract : Introduction: About 25% of patients with COVID-19 develop acute respiratory distress syndrome (ARDS) associated with a high release of pro-inflammatory cytokines such as interleukin-6 (IL-6). The aim of the SARICOR study is to demonstrate that early administration of sarilumab (an IL-6 receptor inhibitor) in hospitalised patients with COVID-19, pulmonary infiltrates and a high IL-6 or D-dimer serum level could reduce the progression of ARDS requiring high-flow nasal oxygen or mechanical ventilation (non-invasive or invasive). Methods and analysis: Phase II, open-label, randomised, multicentre, controlled clinical trial to study the efficacy and safety of the administration of two doses of sarilumab (200 and 400 mg) plus best available therapy (BAT) in hospitalised adults with COVID-19 presenting cytokine release syndrome. This strategy will be compared with a BAT control group. The efficacy and safety will be monitored up to 28 days postadministration. A total of 120 patients will be recruited (40 patients in each arm). Ethics and dissemination: The clinical trial has been approved by the Research Ethics Committee of the coordinating centre and authorised by the Spanish Agency of Medicines and Medical Products. If the hypothesis is verified, the dissemination of the results could change clinical practice by increasing early administration of sarilumab in adult patients with COVID-19 presenting cytokine release syndrome, thus reducing intensive care unit admissions. Trial registration number: NCT04357860 .